2020
DOI: 10.1002/oby.23046
|View full text |Cite
|
Sign up to set email alerts
|

Coding Variants are Relevant to the Expression of Obesity‐Related Genes for Pediatric Adiposity

Abstract: Objective Heredity has a remarkable effect on obesity in an obesogenic environment. Despite the numerous genetic variants that contribute to obesity‐related traits, none has been identified in Chinese children. This study aimed to identify novel variants associated with childhood obesity in China. Methods Promising single‐nucleotide variants were obtained using whole‐exome sequencing from 76 children who had obesity and 74 children with normal weight, and their associations with obesity‐related traits in an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…This case-control study identi ed the genetic association of SULT1A2 rs1059491 variant with obesity in Taizhou adults, and found the G allele over-represented in the normal weight group. However, our previous study indicated that the G allele is a risk factor for obesity in children from northern China [11]. This inconsistency may be due to age and regional differences between the two populations.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…This case-control study identi ed the genetic association of SULT1A2 rs1059491 variant with obesity in Taizhou adults, and found the G allele over-represented in the normal weight group. However, our previous study indicated that the G allele is a risk factor for obesity in children from northern China [11]. This inconsistency may be due to age and regional differences between the two populations.…”
Section: Discussionmentioning
confidence: 87%
“…Assuming a dominant genetic model, an allele frequency of 0.06, and overweight and obesity prevalence of 50% in the adults of China, we estimated that an enrollment target of 466 participants (233 per group) would provide the study with greater than 80% statistical power to detect a signi cant odds ratio of 2.3 for risk of overweight and obesity between the different genotype groups at a signi cance level of 0.05 using a two-tailed test. The anticipated effect size for risk of obesity was determined on the basis of previous data obtained from northern Chinese children and adolescents [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, MAP3K21 is an NIH designated IDG-eligible kinase. Existing reports identify a correlation between MAP3K21 and pediatric obesity, E. coli induced diarrhea, and disease resistance in African chickens [150][151][152].…”
Section: Map3k21mentioning
confidence: 99%